2011
DOI: 10.1186/1475-2859-10-49
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced biosurfactant production through cloning of three genes and role of esterase in biosurfactant release

Abstract: BackgroundBiosurfactants have been reported to utilize a number of immiscible substrates and thereby facilitate the biodegradation of panoply of polyaromatic hydrocarbons. Olive oil is one such carbon source which has been explored by many researchers. However, studying the concomitant production of biosurfactant and esterase enzyme in the presence of olive oil in the Bacillus species and its recombinants is a relatively novel approach.ResultsBacillus species isolated from endosulfan sprayed cashew plantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 41 publications
0
37
0
1
Order By: Relevance
“…The production of surfactin in culture broth of Bacillus subtilis [16], rhamnolipids by Pseudomonas aeruginosa [17], exopolysaccharides in A. calcoaceticus BD4 [18] and rhamnolipid AP-6 in P. fluorescens 378 [19] were all found to be growth associated. In Bacillus subtilis SK320, the production of biosurfactant was also found to be growth associated [3]. Maximum biosurfactant activity was associated with cells at the stationary phase of growth when the nutrient limiting conditions started establishing in the culture medium.…”
Section: Improvement In Biosurfactant Production and Their Applicationsmentioning
confidence: 93%
See 3 more Smart Citations
“…The production of surfactin in culture broth of Bacillus subtilis [16], rhamnolipids by Pseudomonas aeruginosa [17], exopolysaccharides in A. calcoaceticus BD4 [18] and rhamnolipid AP-6 in P. fluorescens 378 [19] were all found to be growth associated. In Bacillus subtilis SK320, the production of biosurfactant was also found to be growth associated [3]. Maximum biosurfactant activity was associated with cells at the stationary phase of growth when the nutrient limiting conditions started establishing in the culture medium.…”
Section: Improvement In Biosurfactant Production and Their Applicationsmentioning
confidence: 93%
“…The total yield reported as g/L was calculated after purifying the biosurfactant using acetone and weighing the lyophilized powder (Figure 1). The recombinant strains not only showed enhanced biosurfactant production, but an increase in the esterase activity as well as surface tension values (Table 4) [3]. Similarly, Bacillus clausii 5B when grown on minimal medium containing 1% (w/v) glucose as carbon source gave the total yield of 2.11 g/L after 96 h [36], whereas Kocuria turfanesis BS-J and Pseudomonas aeruginosa BS-P when grown on combined distillery waste with other industrial wastes showed the biosurfactant production of 0.967 g/L and 1.976 g/L, respectively [37].…”
Section: Improvement In Biosurfactant Production and Their Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operating costs can be brought down by robust wild-type strains or recombinant mutant strains. Testing the possibility of co-products and/or enzymes is another attractive solution to surge the net profitfor example: esterases released during the production of lipopeptides by Bacillus strain and its recombinants (Sekhon et al, 2011. Co-products and by-products are value drivers and increase the economic viability of any business.…”
Section: Biosurfactant's Economic Feasibility-what It Takes To Becomementioning
confidence: 99%